CIRCUIT TECHNOLOGY OF LIGHTGUIDE PYROMETRY IN CASTING AND METALLURGY - A. P. Markov; E. I. Marukovich; E. M. Patuk; Ju. L. Stanulenis; A. G. Starovojtov (Литьë и металлургия)
The modern circuit realizations of structural and algorithmic transformations of pyrometry and thermal control are considered.